Curcumin loaded solid lipid nanoparticles ameliorate adjuvant‐induced arthritis in rats. (17th November 2014) - Arora, R.; Kuhad, A.; Kaur, I.P.; Chopra, K.
Abstract Background Rheumatoid arthritis (RA), a chronic and systemic inflammation, results in destruction of joints and cartilages. Effectiveness of curcumin has been established in a wide variety of inflammatory disorders, but its utility as a therapeutic agent is limited by its poor absorption, rapid metabolism and fast systemic elimination. To apprehend these limitations, we propose to use highly bioavailable curcumin loaded solid lipid nanoparticles (C‐SLNs) for the treatment of RA. Methods In the present study, the protective effect of curcumin and its SLNs was evaluated in complete Freund's adjuvant (CFA)‐induced arthritis in rats. Results Arthritic rats exhibited marked decrease in paw withdrawal threshold in Randall–Selitto and von Frey hair test along with decreased reaction time in hot plate. Arthritic rats also showed significant joint hyperalgesia, joint stiffness and increased paw volume along with marked decrease in mobility score. Arthritic rats showed a significant increase in blood leukocyte count, oxidative‐nitrosative stress, tumour necrosis factor‐α, C‐reactive protein, cyclic citrullinated peptide antibody levels and radiological alterations in tibiotarsal joint. C‐SLN administration (10 and 30 mg/kg), when compared with free curcumin (10 and 30 mg/kg), significantly and dose dependently ameliorated various symptoms of arthritis in rats, improved biochemical markers and preserved radiological alterations in joints of arthritic rats. Conclusions The current findings suggest the protective potential of curcumin‐SLNs in ameliorating CFA‐induced arthritis in rats through attenuation of oxido‐inflammatory and immunomodulatory cascade. Further, the results emphasize that SLNs are a novel approach to deliver curcumin into the inflamed joints and improve its biopharmaceutical performance.